2023
DOI: 10.3390/met13081464
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Amorphous Quasi-High-Entropy Fe-Co-Ni-Cr-(Mo,V)-B Alloys with Various Boron Content

Abstract: This study focuses on the effect of replacing molybdenum with vanadium in rapidly quenched quasi-high-entropy alloys of the Fe-Co-Ni-Cr-(Mo,V)-B system. The paper analyzes the effect of the chemical composition of alloys with different boron content levels on structure formation, characteristic temperatures of alloys, and mechanical properties. An analysis of the relationship between the structure of alloys and their properties is performed. X-ray diffraction and scanning electron microscopy methods were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Ding et al suggested that combining elements from existing quartenary BMGs can also be an effective way of designing quinary HEAAs [61]. Bazlov et al found that the replacement of Mo by V in Fe-Co-Ni-Cr-(Mo, V)-B HEA leads to thermal stability enhancement of the amorphous phase [62]. These works established foundations for subsequent research on HEAAs.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al suggested that combining elements from existing quartenary BMGs can also be an effective way of designing quinary HEAAs [61]. Bazlov et al found that the replacement of Mo by V in Fe-Co-Ni-Cr-(Mo, V)-B HEA leads to thermal stability enhancement of the amorphous phase [62]. These works established foundations for subsequent research on HEAAs.…”
Section: Introductionmentioning
confidence: 99%
“…Various elements were added to the system, mainly IV and V groups of the periodic table, such as Mo, Ti, V, and Nb, as well as Cu, Al, C, etc. [12,[14][15][16][17][18]. The introduction of these elements into the composition of alloys leads to an increase in hardness, strength, corrosion resistance, and a number of other properties.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that not only pure metals, but corresponding ferroalloys, will be used for the smelting of experimental alloys in this study, as well as simpler smelting conditions, it is more appropriate to call the obtained experimental alloys quasi-high-entropy (CES) in the context of pseudo-high-entropy. Such terminology has already been used in other works [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous alloy soft magnetic materials possess high magnetic permeability, elevated electrical resistivity, low coercivity, and minimal core loss. They exhibit facile magnetization and demagnetization processes, surpassing traditional silicon steel sheet materials in soft magnetic performance [1][2][3][4][5]. Electric motors are pivotal power devices in industrial production and daily life, with their electricity consumption ranking at the forefront among various electrical appliances.…”
Section: Introductionmentioning
confidence: 99%